We are preparing the Pan American Congress of Physical Education - García Neira, Carlos (Revista Universidad de Guayaquil, 2008)
The Faculty of Physical Education, Sports and Recreation is located at the University of Guayaquil, in the ’Dr. Salvador Allende’ University City on Fortunato Safadi (Delta) Avenue and Kennedy Avenue, a breeding ground for the best athletes and coaches in Ecuador, whose main authority is Lcdo. Napoleón Gamboa Abril, recently elected. We spoke with him in his office to learn about the reality of this outstanding Academic Unit, who expressed the following: ’We are preparing for the Twenty-First Pan American Congress of Physical Education which we are set to organize here in Ecuador in July 2009.’